Ultrasound assisted synthesis of polyacrylic acid-nanoclay nanocomposite and its application in sonosorption studies of malachite green dye - Sonawane, S. H.; Chaudhari, P. L.; Ghodke, S. A.; Parande, M. G.; Bhandari, Vinay M.; Mishra, Satyendra; Kulkarni, R. D. (Ultrasonics Sonochemistry, 2009)
Synthesis of nanoclay nanocomposite has been undertaken by using polyacryalic acid (PAA) in aqueous medium and ultrasound environment and its application in dye removal has been investigated. The synthesized product was characterized by using FTIR and XRD techniques. The sonosorption capacity of the product namely PAA-nanoclay composite was determined by choosing malachite green (MG) dye as a model pollutant. The effects of various parameters such as nanocomposite loading, pH, various process conditions etc. have been studied. On comparing the results obtained with that of nanoclay as an adsorbent, it was found for an initial concentration of 500 mg/l, the PAA-nanoclay nanocomposite exhibited higher percentage of pollutant removal (68%) and for nanoclay it was 54%. The adsorption data has been correlated using Langmuir and Freundlich models. The fit of the Freundlich isotherm model was found to be good in the entire range of concentration for the experimental sorption data obtained on the nanoclay nanocomposite. A plausible reaction mechanism for use of PAA-nanoclay nanocomposite as ail adsorbent is also proposed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Malachite Green; Nanocomposite; Polyacrylic acid; Sonosorption; Ultrasound

Efficient sorption and photocatalytic degradation of malachite green dye onto NiS nanoparticles prepared using novel green approach - Prasad, Kumar Suranjit; Prajapati, Sheel; Selvaraj, Kaliaperumal (Korean Journal of Chemical Engineering, 2015)
The extract of the Asparagus racemosus leaf tissue works as a stabilizing and capping agent and assists the formation of stable colloidal nanoparticles. Nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX and XRD, respectively. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of near spherical, polydispersed, crystalline NiS of diameter ranging from 4-27 nm. X-ray diffraction studies showed the formation of 110, 101, 300, 021, 220, 221, 131, 410, 401, 321, 330 and 021 planes of hexagonal NiS. EDAX analysis confirmed the presence of Ni and S in nanosphere. The maximum sorption capacity (q (m) ) of NiS nanoparticles for MG dye was found to be 64.85 mg/g. Decolorization as well as disintegration of malachite green under white light illumination was confirmed by LC-MS studies. Results of the present study suggest that nanosized NiS can play an instrumental role in photocatalytic degradation of malachite green dye present in water bodies.
Keywords: Degradation; FTIR; Malachite Green; NiS Nanoparticles; TEM

Dual-functional LaFeO3 perovskites via auto-combustion and hydrothermal methods for gas sensing and photocatalytic dye degradation - Patil, Suraj S.; Shinde, Kiran P.; Patil, Abhijeet P.; Abbas, Muhammad Aoun; Nadargi, Jyoti D.; Mujawar, Sarfraj H.; Mulla, Imtiaz S.; Kim, K. B.; Suryavanshi, Sharad S. (Inorganic Chemistry Communications, 2025)
Integrated environmental remediation is increasingly focused on the development of multifunctional materials capable of simultaneous detection of toxic gases and wastewater treatment. Present study aims to develop dual-functional LaFeO3 perovskites for gas sensing and photocatalytic dye degradation. The nanocrystalline powders of LaFeO3 were synthesized via two distinct methods; auto-combustion (A-LFO) and hydrothermal (H-LFO). Numerous characterization techniques (e.g. XRD, SEM, EDAX, BET, TEM, and XPS) were utilized in order to study the phase, morphology, surface area and elemental composition of A-LFO and H-LFO samples. Both samples were systematically evaluated for their potential in the gas sensing and photocatalytic degradation of malachite green (MG). In results, A-LFO exhibited superior performance in both applications, compared to the H-LFO. It shows similar to 90 % sensitivity for the acetone (500 ppm) at the operating temperature of 275 degrees C and achieved similar to 78 % degradation efficiency for malachite green (MG) dye (5 ppm) within 2 h irradiation of natural sunlight. Although, H-LFO presented comparatively lower performance, both materials demonstrated good selectivity, and stability highlighting their promise as a dual-functional environmental remediation agent. By exploring the performance of the synthesized materials in these dual applications, this research established a relationship between synthesis methods, material properties, and overall performance in environmental and industrial applications, by offering a sustainable and efficient solution to complex pollution challenges.
Keywords: Dye degradation; Gas sensing; LaFeO3; Malachite Green; Perovskites